2019
DOI: 10.21203/rs.2.356/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LASIK-induced Corneal Changes after Correction of Hyperopia with and without Application of Mitomycin-C

Abstract: Background The study aimed to assess the role of intraoperative mitomycin-C (MMC) application during hyperopic LASIK correction (+1.00 D to +6.00 D) by examining topographic corneal changes and incidence of regression over a one-year follow-up period. Methods This comparative randomized control study included 136 eyes of 68 hyperopic patients divided into two groups; Group A included 68 eyes of 34 patients that had LASIK with the application of 0.02% MMC for 10 seconds on the stromal bed after excimer laser… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Topographic stability over one-year follow-up was documented in our study similar to Moawad et al [41] who reported fewer topographic changes after mitomycin C assisted hyperopic LASIK. Gauthier-Fournet et al [42] evaluated the effect of postoperative keratometry on the safety of LASIK for high hyperopia up to 9.5 D and found that corneas with steeper postoperative keratometries were associated with higher loss of CDVA.…”
Section: Discussionsupporting
confidence: 89%
“…Topographic stability over one-year follow-up was documented in our study similar to Moawad et al [41] who reported fewer topographic changes after mitomycin C assisted hyperopic LASIK. Gauthier-Fournet et al [42] evaluated the effect of postoperative keratometry on the safety of LASIK for high hyperopia up to 9.5 D and found that corneas with steeper postoperative keratometries were associated with higher loss of CDVA.…”
Section: Discussionsupporting
confidence: 89%